Između "žrtve u krvi" i najvažnijeg "savezničkog doprinosa": Treći rajh i pitanje jugoistočnoevropske nafte u Drugom svetskom ratu (s posebnim osvrtom na britanske i američke analize - Milan Ristović (Токови историје, 2017)
The plans of the Third Reich to conquer the “living space” in the East of Europe and the great dependence of the German war economy on imports of oil and oil products, after the introduction of the naval blockade, turned it to the only available source of these strategic raw materials, which were located in Southeast Europe. The Romanian oil, new sites in Hungary and other neighbouring countries, the acquisition of the ownership and control over the oil companies which, before the war, belonged to the Western countries and the United States, the imposition of an exclusive right for taking huge quantities of oil for the German war needs, the organization of transport, sabotage prevention, and repairs of refineries after Allied bombing are some of the issues discussed in the text. Attention is also given to the role of Hermann Neubacher, the German special commissioner for the economy.